PHOSPHATIDYLINOSITOL -3KINASE (PI3K) DI PERBENIHAN ADIPOSIT YANG DIPAJAN GLUKOSA TINGGI DENGAN RETINOL - Novi Khila Firani; Bambang Prijadi (Indonesian Association of Clinical Pathologist and Medical laboratory, 2016)
Retinol is one of the active forms of vitamin A. In the previous study, it was known that retinol level in serum of DM patient waslower than in healthy people, which correlated with an increase of the glucose levels in these patients. The importance of retinol in insulinsignaling mechanisms that play a role in the pathogenesis of DM is still unknown. One of the components that play a role in insulinsignaling on adipocytes is phosphatidylinositol-3 kinase (PI3K), which encourages the translocation of glucose transporter-4 (GLUT4) tothe cell surface. The aim of this study was to know the importance of retinol therapy in the levels of PI3K enzyme on visceral adipocyteculture with high glucose exposure (25 mM) as a model of DM in vitro by determination method. Retinol therapy was given at a doseof 0.1 μM, 1 μM , and 10 μM. Measurement of PI3K level was done by ELISA method. The mean (SD) levels of PI3K enzyme were 1.91(0.27), 0.94 (0.15), 1.98 (0.22), 1.69 (0.81), 2.04 (0.16) ng/mL respectively, for adipocyte cultures exposed to 5mM glucose (as aphysiological condition), 25mM glucose, and 25mM glucose concentration with doses of retinol therapy 0.1 μM, 1 μM and10 μM. Theresults of this study indicated that high glucose exposure (25 mM) decreased the level of PI3K compared with adipocyte’s culture on5 mM glucose exposure. Retinol therapy with a dose of 0.1μM, 1μM and10 μM on adipocyte culture exposed with high glucose couldincrease the levels of PI3K.